The Mediating Role of Marketing Strategy in the Effect of Antecedents on Export Performance of Leather and Textile Exporting Companies in Ethiopia (Global Journal of Management and Business Research, 2018)
This study examined the impact of specific firm characteristics, environmental characteristics and marketing mix strategy on export marketing performance. Data were gathered using a structured questionnaire from firms engaged in leather and leather related products, textile and garment exporting companies operating in Ethiopia. Although a total of 278 questionnaires were distributed to a sample of exporter from leather and textile sectors 253 questionnaires were returned at the end of the data collection process, which gave the response rate of 91 per cent. Correlation, regression and path analysis were used to analyse the data. Firm characteristics, Industry characteristics, Export market characteristics, and Product adaptation influence Export performance significantly at 95% confidence interval with a sig. level of 0.000, 0.000, 0.029, and 0.001 respectively. The variable firm characteristics significantly affect export performance and partially mediated by product adaption. When the mediator variable removed from the model its direct value dropped from 0.31 to 0.18 and the direct effect is still significant after mediator enters the model. Product characteristics, export market characteristics and industry characteristics significantly affect export market performance.
Keywords: export; marketing; performance; marketing mix; strategy; leather; textiles ethiopia